MOTIVASI KERJA DENGAN BURNOUT PADA PERAWAT - Tiara Putri Ryandini; Miftahul Munir; mokhamad nurhadi (Jurnal Penelitian, 2021)
Nurse as a profession prosecuted to work in a professional, qualified, and responsible for providing services. A variety of work demands can lead to burnout on nurses, demonstrated by the attitude of the nurses who tends to be cynical about the other person, be indifferent, put up a wry face, temper for no apparent reason, and feeling tired. This research aims to know the relationship of work motivation with burnout on nurses in the Inpatient Installation of RSUD dr. R. Koesma Tuban.The design of this research was analytic correlation with cross sectional approach and a sample of 40 respondents. Sampling technique using cluster sampling and data collection with questionnaires. Research analysis using spearman rank test with significance level α = 0,05.The spearman test results showed there is a relationship of work motivation with burnout on nurses in the inpatient installation of RSUD dr. R. Koesma Tuban with a value of p = 0.001.From the description above it can be concluded that the work motivation can affect the burnout. So, it is expected nurses maintain or increase his work motivation and the hospital must reassess factors supporting the work motivation, in order to the nurse can work optimally and to improve the quality of service and patient care.